Consciousness and confidence. (May 2019) - Rosenthal, David
Abstract: It is natural to see conscious perceptions as typically bringing with them a degree of confidence about what is perceived. So one might also expect such confidence not to occur if a perception is not conscious. This has resulted in the use of confidence as a test or measure of consciousness, one that may be more reliable and fine-grained than the traditional appeal to subjective report as a test for a perception's being conscious. The following describes theoretical difficulties for the use of confidence as a reliable test for consciousness, which show that confidence is less reliable than subjective report. Difficulties are also presented for the use of confidence ratings in assessing degrees of consciousness, which cast doubt on any advantage confidence might have from being more fine-grained than subjective report. And an explanation is proposed for the wide appeal of using confidence to assess subjective awareness, an explanation that also makes clear why confidence is less reliable than subjective report. Highlights: Confidence is less reliable than subjective report in assessing consciousness. Confidence ratings face difficulty even in assessing degrees of consciousness. In unusual cases confidence occurs even when perception is wholly unconscious. Consciousness is theoretically tied to subjective report, but not to confidence. These results independently support higher-order theories of consciousness.